Critical engagement with public sociology : a perspective from the global South - Von Holdt, K. (Karl); Mnwana, Sonwabile; Bezuidenhout, Andries (Public sociology series., 2022)
Involving four generations of Global South researchers, this book provides a theoretical and empirical critique of Burawoy's model of public sociology. It offers a bridge between debates on public sociology and decolonial frameworks.